Green purchasing, green manufacturing, and eco-design: Impact on operational performance - Hendro Setyono; Utik Bidayati; Rikha Muftia Khoirunnisa; Indro Prastowo (Journal of Management and Business Insight, 2025)
Purpose-This study aims to determine the effect of green purchasing, green manufacturing, and eco-design on operational performance. By effectively managing these three environmentally friendly practices, it is hoped that the operational performance of batik micro, small, and medium enterprises can improve significantly. Methodology-The population in this study was micro, small, and medium enterprises producing batik in Yogyakarta, Indonesia. The sample was taken using purposive sampling technique with 122 respondents. The sample was distributed online and offline to micro, small, and medium enterprises producing batik in Yogyakarta. Respondent data were tested using Smart PLS 4.0 with a structural equation model approach covering validity testing, reliability testing, multicollinearity evaluation, and hypothesis testing. Findings-This study found that green purchasing and eco design have a positive impact on operational performance. Meanwhile, green manufacturing does not have a positive impact on operational performance. This condition occurs because most batik micro, small, and medium enterprises in Yogyakarta still face limitations in capital, technology, and resources, so that the manufacturing process cannot be implemented optimally. Research Limitations-This study has limitations due to the small number of respondents and the scope of the research, which focuses on batik micro, small, and medium enterprises in Yogyakarta, so the findings do not represent the green practices of batik micro, small, and medium enterprises in other regions. This research can be expanded to other regions to obtain different findings. Further research can add variables to the research model to predict operational performance. Novelty-This study analyzes the impact of environmentally friendly purchasing, environmentally friendly manufacturing, and environmentally friendly design on the operational performance of batik micro, small, and medium enterprises, which has rarely been researched. The results show the limitations of micro, small, and medium enterprises in implementing environmentally friendly manufacturing, while the effectiveness of operational performance is greatly influenced by the readiness and characteristics of the industrial sector.